Aspects of the composition and origin of achondrites and mesosiderites - Simpson, Alexander Bruce (Department of Geological Sciences, 2026)
[page ii missing] This investigation had as its overall aims the collection and use of both new and existing information on achondritic and mesosideritic meteorites for three main purposes: (1) to establish the relationships between the three major achondrite classes - eucrites, howardites, and diogenites - and to assess the genetic significance of these relationships; (2) to determine whether the apparent similarity between the so-called basaltic achondrites (eucrites and howardites) and the silicate portions of mesosiderites is indicative of a genetic connection; and (3) to formulate, if possible, a model for the origin of the achondrites based on all available data. The starting point for the inves~igation was defined by a critical review and systematization of relevant information scattered throughout the literature up to the end of 1973. The formation of the howardites, a range of polymict breccias with compositions that vary in a serial fashion between those of eucrites and diogenites, was investigated by a study of their petrography and by an extensive programme of electron microprobe analysis aimed at determining the extent of compositional variation present in their constituent mineral, lithic, and glassy phases. Four howardites chosen to represent the class - Bununu, Frankfort, Malvern, and Molteno - were so examined. A fifth meteorite, Binda, conventionally classed as a howardite (HEY, 1966) but later regarded as a cumulate eucrite (STOLPER, 1975a,b), was included for comparison with the howardites in the full realisation that its classification was problematical. Compositional data on 1,634 clasts in these five breccias were obtained from 2,938 microprobe analyses. The phases analyzed were pyroxene, plagioclase, olivine, silica minerals, chromite, ilmenite, meta-1,, troilite, glass,- and glassy microbreccia. University of Cape Town - xxi - A comprehensive study of inter-element relationships, particularly of those involving refractory elements, was carried out to establish the relations between the three main achondrite classes and between th~ basaltic achondrites and the silicate fractions of mesosiderites for the purpose of gaining information on the possible modes of origin of these meteorites. Additional evidence on the genesis_ of the eucrites was obtained from mathematical modelling. These studies were based on the concentrations of major, minor, and trace elements in 42 bulk analyses of achondrites and mesosiderites.· .Most of the achondrites used were previously analyzed in this labora~ory (McCARTHY, 1971; McCARTHY et al., 1972), but new analyses for 23 elements were performed by X-ray fluorescence spectrometry on five achondrite samples (Binda, Kapoeta, Molteno, and two samples.of Malvern) and on the silicate fractions of seven mesosiderites (Fmery, Estherville, .J:;owicz, Mincy, Mount Padbury, Patwar, and Va~a Muerta). The accumulated petrographic and compositional data were used to evaluate existing hypotheses of achondrite formation. These were: (1) evolution of the achondrites from a common magmatic source by igneous differentiation, diogenites being the cumula~es and eucrites the late-stage liquids produced by this process, which was followed by brecciation (e.g. DUKE and SILVER, 1967); (2) formation of the howardites by mixing, in vary~ ing proportions; of compositionally restricted diogenitic and eucritic materials and a minor chondritic component (JEROME and GOLES, 1971); and (3) genesis· of the eucrites by small degrees of low pressure partial fusion of a source region in the parent body, possibly followed by production of the more magnesian materials present in diogenites and howardites by further partial melting of the residues (STOLPER, 1977a). It was concluded that a twocomponent mixing model does not explain the observational data. The compositional bimodality of howarditic pyroxenes implicit in such a model is absent University of Cape Town - xxiii - of the mesosiderites by mixing of metal and howarditic or eucritic material. It was noted, however, that the higher content of FeO in howardites constitutes the main difference between them and the mesosideritic silicates. Recalculation of analyses after subtraction of 'excess' FeO, FeS, and P 2 o5 and Ni (assumed to be associated with the metal phase) resulted in coincidence of achondritic and mesosideritic trends in plots of major element relationships. This prompted the proposal that the source material of the achondrites - approximately represented by the average howardite - was formed from the most reduced, 'primitive' mesosiderites by oxidation of the high metal content of these mesosiderites, and that lesser degrees of oxidation produced mesosiderites with silicates compositiona~ intermediate to those of howardites and 'primitive' mesosiderites. These proposed relationships could be demonstrated, within reasonable limits of accuracy, for the major element concentrations of the 42 meteorites included in. the study but not satisfactorily for the trace elements, possibly because of their redistribution during later, depth-related metamorphism of the 'primitive' mesosiderites. It was deduced that the source material thus produced (from which the achondrites were derived) consisted of approximately 90% pyroxene (Wo5En65 ), 5% plagioclase (An94), and 5% Cr-rich spinel; this is one of the alternatives proposed by STOLPER (1977a). The composition calculated from this mode plots on the olivine-pyroxene phase boundary of the silica-olivineanorthite pseudo-ternary diagram (WALKER et al., 1972). The trend defined by the diogenites and howardites, whose more magnesian components are presumably attributable to the second stage of partial melting of the source region, also lies on this boundary. The close relationship between the calculated composition of the source material of the achondri~es, which is similar to other estimates made (e.g. DREIBUS et al., 1977), and the observed trend of University of Cape Town - xxiv - the diogenites and howardites is of significance to the genetic model presented below. Investigation of the petrography and phase chemistry of Binda showed that although some compositional variation - possibly attributable to minor fractionation - occurs in its constituent pyroxene and plagioclase and a small amount of glassy material is present, it is essentially a monomict breccia with a formational history different from the howardites. that it resembles compositionally. It is a slowly-cooled cumulate that has been subjected to brecc_iation and cataclastic action in situ, without necessarily having been part of a regolith on its parent body. It was concluded from the study of inter-element relationships that it is neither a howardite nor a cumulate eucrite. Its constant association with mesosideritic silicates in plots of these relationships, together with its depletion in trace elements and metal, suggests that it is a silicate 'clot' from a fairly highly-oxidized mesosiderite .. The model proposed on the basis of the present investigation envisages formation of the achondrites in a parent body of asteroidal dimen9 sions that accreted about 4.6 x 10 years ago from nebular material with abundances that were near-chondritic apart from depletion in volatiles. This body, for which 4 Vesta is a possible choice (CONSOLMAGNO and DRAKE, 1977), was heated by external sources and underwent primary differentiation during, or immediately following, accretion. Metal-silicate segregation was probably incomplete, and a pallasitic zone may have formed at depth in the body. It is proposed that at least the outermost parts of the body (subsequently to become outer mantle) were composed of material similar to the mesosiderites regarded as 'primitive'. Progressive oxidation of this material, possibly accompanied by segregation of metal, generated the pyroxene-rich rocks that were parental to the achondrites. Partial fusion of these source rocks University of Cape Town - xxv - pr,oduced the 'primary' eucritic melts from which Fe-rich residual liquids and complementary cumulates were formed by fractional crystallization~ this process continuing until plagioclase was exhausted from the source region. Eruption of the eucritic melts, possibly when a critical degree of partial melting had been attained, resulted in the formation of a crust in at least part of the parent body. The residues from this first stage of partial fusion constitute a series of pyroxenites ranging from the most Fe-rich diogenite hitherto reported (Yamato 75032) to the 1 normal 1 diogenites. If all plagioclase-bearing melts were removed from the source region(s), no further melting took place and only eucritic and diogenitic series were produced. If, however, some of the initial melts remained trapped in the residues, further addition of heat to the source region would have caused a second stage of partial fusion in which a range of pyroxeneplagioclase melts compositionally intermediate to the 'primary' eucrites and the new source material (residues + trapped feldspar-bearing liquids) was generated. These intermediate melts represent some of the components of howardites that were not contributed by eucrites or diogenites. Other such components ~ orthopyroxenes more magnesian than those of the diogenite series - were formed in the residues from the second stage of partial melting· after exhaustion of trapped plagioclase-bearing melt. The outermost parts of the parent body therefore presented, as a consequence of the interaction of processes of partial melting and crystallization differentiation, a wide compositional spectrum of materials for brecciation and mixing by impacting projectiles. In the regolith so formed, howardites and polymict eucrites were produced according to whether _the material incorporated in them was biased towards the orthopyroxenitic residues or towards members of the eucrite series. Intrusive impact melts were formed locally and retained inclusions of the metal of the impacting bodies. University of Cape Town ·xxvi - Lithification ' of the regolith and ejection of material from it produced the polyrnict achondritic breccias. Moncmict breccias probably represent rocks that either were fanned at depth in the crust of the parent body (e.g. residues and cumulates) or were protected by an overlying regolith deposit from all but the most violent impacts.